2018
DOI: 10.1002/acp.3446
|View full text |Cite
|
Sign up to set email alerts
|

Are you for real? Exploring language use and unexpected process questions within the detection of identity deception

Abstract: The current study was to test whether reality monitoring and language use could distinguish identity liars from truth tellers when answering outcome questions and unexpected process questions. Truth tellers (n = 30) and liars (n = 30) discussed their identity in a recruitment interview. No differences emerged between truth tellers and liars in the details they provided. In terms of language use, liars used more positive language than truth tellers, whereas truth tellers used more cognitive process words than l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 89 publications
(122 reference statements)
0
2
0
1
Order By: Relevance
“…To date, over 150 unique cues to deceit have been examined in the deception literature (DePaulo et al 2003). This includes specific behaviors, such as foot and leg movements (deTurck & Miller, 1985); more holistic person judgements, such as pleasantness and friendliness (Burgoon et al, 1996); verbal cues, such a statement detail (Köhnken et al, 1995) and consistency (Granhag & Strömwall, 1999); para-verbal cues, such as pitch (Motley, 1974) and speech rate (Riggio & Friedman, 1983); as well as linguistic cues, such as pronoun use (Newman et al, 2003) and language positivity (Jupe et al, 2018). Indeed, virtually any observable behavior can be examined as a potential cue to deception.…”
Section: Empirical Research On Cues To Deceptionmentioning
confidence: 99%
“…To date, over 150 unique cues to deceit have been examined in the deception literature (DePaulo et al 2003). This includes specific behaviors, such as foot and leg movements (deTurck & Miller, 1985); more holistic person judgements, such as pleasantness and friendliness (Burgoon et al, 1996); verbal cues, such a statement detail (Köhnken et al, 1995) and consistency (Granhag & Strömwall, 1999); para-verbal cues, such as pitch (Motley, 1974) and speech rate (Riggio & Friedman, 1983); as well as linguistic cues, such as pronoun use (Newman et al, 2003) and language positivity (Jupe et al, 2018). Indeed, virtually any observable behavior can be examined as a potential cue to deception.…”
Section: Empirical Research On Cues To Deceptionmentioning
confidence: 99%
“…Researchers have recently employed techniques such as the unexpected-question method to detect identity deception. Jupe et al 70 investigated whether contextual and perceptual details and language use could effectively differentiate identity deceivers from truth tellers in response to outcome questions (related to the outcome of an event) and unexpected process questions (specific to the planning phase or the progression experience of an event). Contrary to expectations, the findings suggested that contextual and perceptual details may not have diagnostic value when applied to the cross‐situational domain of identity deception.…”
Section: Introductionmentioning
confidence: 99%
“…These commentaries covered the essential subjects regarding human judgements of deception and highlighted paramount issues on which researchers should focus. However, computational linguistic deception detection is barely mentioned in the publication of this 3-day workshop, while the interest for these tools and methods increases (e.g., Jupe et al, 2018;Kleinberg et al, 2018;Tomas et al, 2021c).…”
Section: Introductionmentioning
confidence: 99%